Amputating the Long Arm of the Law: An Analysis of the U.S. Supreme Court's Decision in Morrison and Why § 10(B) Still Reaches Issuers of ADRs - Paul B. Maslo (Washington University Law Review, 2011)
This Article reviews the conduct and effects tests and the Supreme Court‘s decision in Morrison. It then addresses the new transactional rule‘s impact on the application of the Exchange Act‘s antifraud provisions in several situations where courts before Morrison routinely allowed § 10(b) claims to proceed: (1) foreign-cubed actions (i.e., claims involving a foreign citizen‘s purchase of a foreign issuer‘s ordinary shares on a foreign exchange) where the fraud impacts U.S. investors or is executed in the U.S.; (2) cases involving a U.S. citizen‘s purchase of a foreign issuer‘s ordinary shares outside the U.S.; and (3) actions concerning the purchase of a foreign issuer‘s American Depository Receipts ("ADRs"). While courts are in agreement that the test articulated in Morrison prevents § 10(b) from reaching defendants in the first and second types of actions, they are in conflict as to whether ADR purchasers should be able to bring a claim. This Article argues that a recent district court decision wrongly decided the application of Morrison in the ADR context and that the new rule should not prevent most ADR purchasers from bringing a cause of action under § 10(b).
Keywords: Morrison v. National Australia Bank 130 S. Ct. 2869 (2010); Class action lawsuits; Extraterritoriality; Securities fraud; Securities Exchange Act; United States